Not Dead Yet: High Redshift Recently Quenched Galaxies As Probes Of Galaxy Evolution - Taylor, Elizabeth (2025)
In this thesis, we explore the roles that galaxy environment, stellar mass and outflows play in the quenching of star formation, by studying recently quenched galaxies at cosmic noon and beyond (0.5 < z < 4.4). We utilise photometric data from the UKIDSS Ultra Deep Survey (UDS), the deepest NIR survey over ∼1 deg2, which has sufficient volume to enable samples to be split by stellar mass, redshift and environment. Additionally, we use spectroscopic data for galaxies within the UDS field, from deep observations at ESO VLT (UDSz, VANDELS) and JWST NIRSpec (EXCELS), to study galactic scale winds in the interstellar medium.